Agile Application-Aware Adaptation for Mobility - Noble, Brian; Satyanarayanan, M.; Narayanan, Dushyanth; Tilton, Eric; Flinn, Jason; Walker, Kevin (Proceedings of the 16th ACM Symposium on Operating System Principles (SOSP '97), 1997)
In this paper we show that application-aware adaptation, a collaborative partnership between the operating system and applications, offers the most general and effective approach to mobile information access. We describe the design of Odyssey, a prototype implementing this approach, and show how it supports concurrent execution of diverse mobile applications. We identify agility as a key attribute of adaptive systems, and describe how to quantify and measure it. We present the results of our evaluation of Odyssey, indicating performance improvements up to a factor of 5 on a benchmark of three applications concurrently using remote services over a network with highly variable bandwidth.